Design and synthesis of propellane derivatives and oxa-bowls via ring-rearrangement metathesis as a key step - Kotha, Sambasivarao; Gunta, Rama (Beilstein Journal of Organic Chemistry, 2015)
Various intricate propellane derivatives and oxa-bowls have been synthesized via a ring-rearrangement metathesis (RRM) as a key step starting from readily accessible starting materials such as p-benzoquinone, 1,4-naphthoquinone and 1,4-anthraquinone.
Keywords: allylation; propellane derivatives; quinones; ring-rearrangement metathesis

The Logic of Chemical Synthesis - Corey, E. J.; Cheng, X.-M. (John Wiley & Sons, 1989)

Design and Strategy in Organic Synthesis - Hanessian, S.; Giroux, S.; Merner, B. L. (Wiley-VCH, 2013)

Organic Synthesis: Strategy and Control - Wyatt, P.; Warren, S. (John Wiley & Sons, 2013)

Organic Synthesis: The Science Behind the Art - Smit, W. A.; Bochkov, A. F.; Caple, R. (Royal Society of Chemistry, 1998)

Classics in Hydrocarbon Chemistry - Hopf, H. (Wiley-VCH, 2000)

The Way of Synthesis: Evolution of Design and Methods for Natural Products - Hudlicky, T.; Reed, J. W. (Wiley-VCH, 2007)

Classics in Total Synthesis: Targets, Strategies, Methods - Nicolaou, K. C.; Sorensen, E. J. (Wiley-VCH, 1996)

(untitled) - Holub, N.; Blechert, S. (Chem. – Asian J., 2007)
And references cited therein.

Olefin Metathesis: Theory and Practice, Part I - Schmidt, B.; Krehl, S. (Domino and Other Olefin Metathesis Reaction Sequences, 2014)

(untitled) - Nolan, S. P.; Clavier, H. (Chem. Soc. Rev., 2010)

(untitled) - Kotha, S.; Ravikumar, O. (Eur. J. Org. Chem., 2014)

(untitled) - Kotha, S.; Gunta, R. (Beilstein J. Org. Chem., 2015)

Handbook of Metathesis - Grubbs, R. H.; O'Leary, D. J. (Wiley-VCH, 2015)

(untitled) - Kotha, S.; Misra, S.; Sreevani, G.; Babu, B. V. (Curr. Org. Chem., 2013)

(untitled) - Kotha, S.; Dipak, M. K. (Tetrahedron, 2012)

(untitled) - Kotha, S.; Krishna, N. G.; Halder, S.; Misra, S. (Org. Biomol. Chem., 2011)

(untitled) - Kotha, S.; Meshram, M.; Tiwari, A. (Chem. Soc. Rev., 2009)

(untitled) - Kotha, S.; Lahiri, K. (Synlett, 2007)

(untitled) - Kotha, S.; Sreenivasachary, N. (Indian J. Chem., Sect. B, 2001)

(untitled) - Kotha, S.; Mandal, K. (Tetrahedron Lett., 2004)

(untitled) - Kotha, S.; Chinnam, A. K. (Synthesis, 2014)

(untitled) - Kotha, S.; Chinnam, A. K.; Tiwari, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Kotha, S.; Chavan, A. S.; Dipak, M. K. (Tetrahedron, 2011)

(untitled) - Kotha, S.; Dipak, M. K. (Chem. – Eur. J., 2006)

(untitled) - Gharpure, S. J.; Porwal, S. K. (Org. Prep. Proced. Int., 2013)
And references cited therein.

(untitled) - Kotha, S.; Ravikumar, O. (Tetrahedron Lett., 2014)

(untitled) - Kotha, S.; Chavan, A. S.; Goyal, D. (ACS Comb. Sci., 2015)

(untitled) - Kotha, S.; Brahmachary, E.; Sreenivasachary, N. (Tetrahedron Lett., 1998)

Propellanes: Structure and Reactions - Ginsburg, D. (Verlag Chemie, 1975)

Propellanes: Structure and Reactions: Sequel I - Ginsburg, D. (Technion, 1981)

Propellanes: Structure and Reactions: Sequel II - Ginsburg, D. (Technion, 1985)

(untitled) - Mal, D.; Ray, S. (Eur. J. Org. Chem., 2008)

(untitled) - Valderrama, J. A.; Espinoza, O.; González, M. F.; Tapia, R. A.; Rodríguez, J. A.; Theoduloz, C.; Schmeda-Hirschmann, G. (Tetrahedron, 2006)
And references cited therein.

(untitled) - Hua, D. H.; Tamura, M.; Huang, X.; Stephany, H. A.; Helfrich, B. A.; Perchellet, E. M.; Sperfslage, B. J.; Perchellet, J.-P.; Jiang, S.; Kyle, D. E.; Chiang, P. K. (J. Org. Chem., 2002)

(untitled) - Patney, H. K.; Paddon-Row, M. N. (Synthesis, 1986)

(untitled) - Kotha, S.; Banerjee, S. (RSC Adv., 2013)

Diversity-Oriented Synthesis: Basics and Applications in Organic Synthesis, Drug Discovery, and Chemical Biology - Trabocchi, A. (John Wiley & Sons, 2013)